Pinjaman Online dalam Ekosistem Ekonomi Digital Indonesia: Analisis Dampak terhadap Inklusi Keuangan dan Pertumbuhan Ekonomi - Riko Andi Setiawan (CV. ITTC INDONESIA, 2026)
The digital economic transformation in Indonesia has driven the growth of technology-based financial services (financial technology/fintech), especially online loans or peer-to-peer (P2P) lending. The presence of online loans provides a faster, easier, and more inclusive financing alternative compared to conventional financial institutions, especially for people who are not yet reached by banking services (unbanked and underbanked). On the other hand, the growth of the online loan industry also brings various challenges, such as increased risk of bad credit, illegal lending practices, misuse of personal data, and low financial literacy among the public. This study aims to analyze the impact of the development of online loans on improving financial inclusion and Indonesia's economic growth within the digital economy ecosystem. The research method used is qualitative research with a library research approach by analyzing various scientific journals, official government reports, and data from the Financial Services Authority (OJK), Bank Indonesia (BI), and the Central Statistics Agency (BPS) published during the 2021–2026 period. The analysis was conducted using a descriptive-analytical method by comparing various previous research results. The findings show that online loans contribute positively to increasing financial inclusion by expanding access to financing for MSME players and people who previously had difficulty obtaining bank credit. In addition, the increase in digital financing distribution also boosts economic activity, household consumption, small-scale investment, and micro-business growth. However, the effectiveness of that contribution is largely influenced by the quality of regulations, industry supervision, consumer protection, and the improvement of the public's digital financial literacy. Therefore, strengthening the governance of the fintech lending industry becomes a key factor in maintaining the sustainability of online loans' contribution to national economic development.